Oral administration of a specific kynurenic acid synthesis (KAT II) inhibitor attenuates evoked glutamate release in rat prefrontal cortex. (15th July 2017) - Bortz, D.M.; Wu, H.-Q.; Schwarcz, R.; Bruno, J.P.
Abstract: Cognitive deficits represent core symptoms in schizophrenia (SZ) and predict patient outcome; however, they remain poorly treated by current antipsychotic drugs. Elevated levels of the endogenous alpha7 nicotinic receptor negative allosteric modulator and NMDA receptor antagonist, kynurenic acid (KYNA), are commonly seen in post-mortem tissue and cerebrospinal fluid of patients with SZ. When acutely or chronically elevated in rodents, KYNA produces cognitive deficits similar to those seen in the disease, making down-regulation of KYNA, via inhibition of kynurenine aminotransferase II (KAT II), a potential treatment strategy. We determined, in adult Wistar rats, if the orally available KAT II inhibitor BFF816 a) prevents KYNA elevations in prefrontal cortex (PFC) after a systemic kynurenine injection and b) reverses the kynurenine-induced attenuation of evoked prefrontal glutamate release caused by stimulation of the nucleus accumbens shell (NAcSh). Systemic injection of kynurenine (25 or 100 mg/kg, i.p.) increased KYNA levels in PFC (532% and 1104% of baseline, respectively). NMDA infusions (0.15 μg/0.5 μL) into NAcSh raised prefrontal glutamate levels more than 30-fold above baseline. The two doses of kynurenine reduced evoked glutamate release in PFC (by 43% and 94%, respectively, compared to NMDA alone). Co-administration of BFF816 (30 or 100 mg/kg, p.o.) with kynurenine (25 mg/kg, i.p.) attenuated the neosynthesis of KYNA and dose-dependently restored NMDA-stimulated glutamate release in the PFC (16% and 69%, respectively). The ability to prevent KYNA neosynthesis and to normalize evoked glutamate release in PFC justifies further development of KAT II inhibitors for the treatment of cognitive deficits in SZ. Highlights: Kynurenine increases KYNA and attenuates evoked glutamate release in PFC. BFF816 decreases basal and elevated KYNA in PFC. BFF816 rescues kynurenine-induced reductions in evoked glutamate in PFC. Control of KYNA levels justifies the use of KAT II inhibitors for treatment in SZ.